# 8/(x-2)-4x(x+2)=32/(x^2-4)

## Simple and best practice solution for 8/(x-2)-4x(x+2)=32/(x^2-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 8/(x-2)-4x(x+2)=32/(x^2-4) equation:

8/(x-2)-4x(x+2)=32/(x^2-4)
We move all terms to the left:
8/(x-2)-4x(x+2)-(32/(x^2-4))=0

Domain of the equation: (x-2)!=0
We move all terms containing x to the left, all other terms to the right
x!=2
x∈R

Domain of the equation: (x^2-4))!=0
x∈R

We multiply parentheses
-4x^2+8/(x-2)-8x-(32/(x^2-4))=0
We calculate fractions

-4x^2+8x^2/((x-2)*(x^2-4)))+(-8x-(32*(x-2))/((x-2)*(x^2-4)))=0

We calculate terms in parentheses: -(32*(x-2))/((x-2)*(x^2-4))), so:
32*(x-2))/((x-2)*(x^2-4))
We multiply all the terms by the denominator

32*(x-2))
We multiply parentheses
32x+
We add all the numbers together, and all the variables
32x
Back to the equation:
-(32x)

We add all the numbers together, and all the variables
-4x^2+8x^2/((x-2)*(x^2-4)))+(-40x=0
We multiply all the terms by the denominator

8x^2-4x^2*((x-2)*(x^2-4)))+(-40x*((x-2)*(x^2-4)))+(=0

`